Septostomy during laser surgery for twin-to-twin transfusion syndrome - Andrei E. Bugerenko; Liya N. Shcherbakova; Olga B. Panina (IP Berlin A.V., 2021)
Aim. To assess the perinatal outcomes of monochorionic diamniotic (MCDA) pregnancy after fetoscopic laser coagulation of anastomoses (FLCA) performed for twin-to-twin transfusion syndrome (TTTS), accompanied by induced or unintentional septostomy, and to identify the factors leading to septostomy. Materials and methods. The retrospective study included 231 cases of FLCA performed in pregnant women with TTTS: in 19 cases septostomy was performed, and in 212 cases intertwin membrane remained intact. Results. The incidence of septostomy during FLCA for TTTS was 8.2%. In 47.3% the rupture of the intertwin membrane occurred during trocar insertion (unintentional septostomy); in 42.1% septostomy was needed to perform laser coagulation of anastomoses located on the placental surface in the donor's amnion (forced septostomy). The placenta was located on the anterior uterine wall in 78.9% in the septostomy group and in 47.6% with an intact intertwin membrane (p=0.01). Anastomoses were located on the donor half of the placenta significantly more often when septostomy was needed to perform selective coagulation of anastomoses located far from the intertwin membrane and obstructed by the body of the donor fetus (42.1%). In 15.8% of patients with septostomy and 2.4% with intact intertwin membrane, umbilical cords of the donor and the recipient fetus were attached closer than 2 cm to each other (p=0.003). In the septostomy group premature rupture of membranes was more frequent (42.1% vs 18.4%, p=0.03) and a delivery time was shorter [26.3 (18.0, 37.0) vs 34.4 (20.3, 40.0) weeks, respectively, p=0.01] than in patients with an intact intertwin membrane. The survival rate after FLCA was lower after septostomy compared to intact intertwin membrane: at least one of the twins survived in 47.4% vs 80.7%, respectively (p=0.002), both fetuses survived in 36.8% vs 75.0%, respectively (p=0.001). Logistic regression analysis showed increased risk of septostomy in patients with the anastomoses located on the donor half of the placenta and when the donor and the recipient umbilical cords are attached close to each other, regardless of the localization of the placenta, gestational age and the stage of TTTS. Conclusion. Lower incidence of unintentional septostomy during FLCA achieved by using modern equipment and surgical techniques will lead to better perinatal outcomes in patients with MCDA twins with TTTS.